Molybdenum disulfide-Zirconium dioxide composite with enhance supercapacitance performance - NADHIM SHAKER, Razan; MOHAMMED, Sami; ABDULSAYED, Yousra Ali (Journal of Metals, Materials and Minerals, 2023)
As a supercapacitor active material, molybdenum disulfide (MoS2) layer offers good conductivity, large surface area, and electrochemical stability. In practice, however, its capacitance is low in comparison to other materials. This work synthesized MoS2-zirconium dioxide (ZrO2) composite in a simple, high-throughput way to test it as a supercapacitor active layer. During the tests, the composite shows a gravimetric capacitance of 500.0 F⸳g-1, while MoS2 and ZrO2 have capacitances of 265.12 and 152.43, respectively. The increase in capacitance of composite stems from the synergistic effect between ZrO2’s pseudocapacitor behavior and MoS2’s electric double layer capacitance (EDLC). Moreover, the composite has a discharge time of 406 s at a current density of 1 A⸳g-1, which is much longer compared to MoS2 and ZrO2. The stability test of the composite also shows that it maintains 93% of its initial capacitance after 2000 charge/discharge cycles.